Ocular mucous membrane pemphigoid: novel treatment strategies. Issue 5 (15th October 2021) - Jabbour, Samir; Phylactou, Maria; Ahmad, Sajjad
Abstract : Purpose of review: To describe current treatments of ocular mucous membrane pemphigoid (OMMP), including conventional systemic immunosuppression (CIST) and novel biologic agents. Recent findings: CIST remains the main stay therapy for the management of OMMP. The choice of agents is tailored to disease severity – mild disease is treated with dapsone, whereas moderately severe cases are often treated with mycophenolate mofetil or sulfa-based drugs and severe cases are treated with cyclophosphamide. In recalcitrant disease newer biologics such as Rituximab, intravenous immunoglobins and tumour necrosis alpha antagonists have proven to be effective in disease control. Control of inflammation with topical therapy and halting conjunctival fibrosis remain as areas of unmet clinical needs. Summary: OMMP is largely treated with CIST. The recent introduction of new biologic agents could shape the way the disease is treated in the near future.